Menangani Ekstramisme Dan Membina Moderasi Beragama Di Sekolah: Praktik Terbaik Dan Pembelajaran - Fathan Fihrisi; Krisna Putra Alliandra; Firlya Ika Septiviana; Ummi Zahrotul Ainiyah; Khudzaifah Nuqia; Diana Erista Ferli; Ervinatus Tri Wulansari; Ummi Qonitatin (Peneliti.net, 2023)
This article discusses the importance of addressing extremism and fostering religious moderation in educational environments, particularly in schools. Religious extremism has become a growing concern in many countries, and schools play a crucial role in preventing and addressing this phenomenon. In this article, we analyze the best practices that can be implemented in schools to promote religious moderation and tackle extremism. Some of the best practices discussed include developing educational curricula that encompass understanding and appreciation of religious diversity, employing interreligious dialogue approaches, providing teacher training on recognizing and addressing extremism, and actively involving communities in religious education. By implementing these practices, schools can create inclusive, tolerant, and respectful environments.